Aplikasi Sistem Penjadwalan Imunisasi Bayi Berbasis Web Pada Rumah Sakit Ibu dan Anak (RSIA) Vitalaya - Tia Febriani; Fajar Agung Nugroho (CV. Multi Kreasi Media, 2022)
Immunization is an activity carried out to form a person's immunity by giving vaccines to stimulate the immune system to be immune to disease and reduce mortality every year. The immunization scheduling process in each hospital usually uses different methods, some are still manual and some are already using online-based methods. RSIA Vitalaya still uses the method of recording in the KIA book so it is feared that the immunization data will be wrong and immunizations will be given repeatedly. To provide a solution to the problems above, the authors make a system application that can help the immunization disability process. As well as making it easier for the hospital to schedule the next immunization so that there are no mistakes in giving immunizations. The process of collecting data in this system uses the method of observation, interviews and literature study. The development method uses the waterfall method which is a systematic information system development model from one stage to another, starting from the requirements analysis stage, system design, program code writing, system testing and program implementation and maintenance. The expected result in this application system is to facilitate immunization scheduling so that there are no errors in the next immunization. Provide immunization scheduling information for the baby's parents as a reminder for the next immunization.